UV-VIS, Fluorescence and Mass Spectrometry Investigation on the Transition Metal Ion Chelation of Two Bioisosteres of Resveratrol - Qin, Wen; Zou, Biqun; Zhang, Ye; Yi, Xianghui; Pan, Zhenghong (Asian Journal of Chemistry, 2012)
2-[(o-Hydroxylphenylimino)methyl]phenol (OSAP) and 2-((p-hydroxylphenylimino)methyl)phenol (PSAP), two bioisosteres of the natural antioxidant resveratrol, are biologically interesting antioxidants. In order to probe whether they exert their antioxidant effect through metal ions chelation, the Cu(II) ion and Fe(II) ion chelating abilities of these compounds were measured by UV-VIS, fluorescence and mass spectroscopy, respectively. From UV-VIS spectra, the binding constants of OSAP with Cu2+ and Fe2+ were determined to be 7.58 × 103 and 2.22 × 103 M-1 by Benesi-Hildebrand method, while that of PSAP were found to be 6.20 × 103 and 2.08 × 104 M-1, respectively. From fluorescence quenching spectra, the Stern-Volmer quenching constants of OSAP with Cu2+ and Fe2+ were assessed to be 6.06 × 104 and 6.70 × 104 M-1, respectively, while that of PSAP were calculated to be 8.45 × 104 and 1.43 × 105 M-1. In addition, mass spectrometry studies showed that both OSAP and PSAP formed a 2:1 complex with ferrous when they were treated with Fe2+ in a 8:2 (v:v) methanol-water solution, respectively. The above results demonstrated the relatively significant role of the transition metal ion chelation in their antioxidant abilities.